Fractionation of Ni, Cr and Cu from Soil by Sequential Extraction Procedure and Determination by Inductively Coupled Plasma Optical Emission Spectrometry - Akkus, Sukran; Bal, Tulin; Karaaslan, Nagihan M.; Yaman, Emre; Kilinc, Ersin; Yaman, Mehmet (Wiley, 2013)
Five-step sequential extractions were employed to fractionation of Ni, Cr and Cu in soil polluted by anthropogenic activities and determine the mobility of the metals. Twelve samples were collected on an agricultural area that was located near an airport and intercity roads in Elazig-Turkey. Exchangeable, organically bounded, carbonate bounded, adsorbed species on Fe and Mn oxides and residual species (except silicates) of Ni, Cr and Cu were extracted into solution by using CaCl2, Na4P2O7, Na(2)EDTA, NH2OH-HCl and HNO3-H2O2, respectively. Mobile metal concentrations in fractions and total recoverable in soils were determined by using inductively coupled plasma-optical emission spectrometry (ICP-OES). Total recoverable Ni, Cr and Cu concentrations were in the range of 40-119, 45-126 and 23-72mgkg(-1), respectively. It was observed that total concentrations of metals in some of the samples were higher than the permitted values. The sum of the mobile percentages of metals was found to be lower than 50%. The Ni, Cr and Cu percentages for exchangeable species are in the ranges of 0.18-1.64, 0.03-0.59 and 0.42-2.53%, respectively.
Keywords: Environmental pollution; ICP-OES; Metal mobility; Sequential extraction; Toxic metals